Am atasat aici o rezolvare, succes!
[tex]1. \frac{9}{15} + ( \frac{8}{15} - \frac{2}{15} ) = \frac{9}{15} + ( \frac{8-2}{15}) = \frac{9}{15} + \frac{6}{15} = \frac{9+6}{15} = \frac{15}{15} = \frac{1}{1} = 1\\\\\\\\2. (\frac{5}{9} + \frac{4}{9}) - \frac{7}{11} = (\frac{5+4}{9} ) - \frac{7}{11} = \frac{9}{9} - \frac{7}{11} = \frac{99}{99} - \frac{63}{99} = \frac{99-63}{99} = \frac{36}{99} = \frac{4}{11}\\\\\\3. \frac{4}{8} + \frac{5}{16} = \frac{8}{16} + \frac{5}{16} = \frac{8+5}{16} = \frac{13}{16}[/tex]